Roles of miR-10a-5p and miR-103a-3p, Regulators of BDNF Expression in Follicular Fluid, in the Outcomes of IVF-ET - Zhang, Qiyao; Su, Jinfeng; Kong, Wei; Fang, Zhou; Li, Yan; Huang, Ziqiang; Wen, Ji; Wang, Yue (Frontiers in Endocrinology, 2021)
Brain-derived neurotrophic factor (BDNF), a member of the neurotrophin family, plays critical roles in the physiological process of oocyte mature and IVF outcomes of patients with infertility. However, the regulation of BDNF expression in the microenvironment surrounding the oocyte is still unknown. We initially predicted some microRNA (miRNA) candidates targeting bdnf with a series of bioinformatics analysis tools to determine the underlying regulatory mechanisms of BDNF, particularly the effect of miRNAs on BDNF expression. Then, we assessed whether the expression of these 14 selected miRNAs was negatively associated with BDNF expression in follicular fluid (FF) samples obtained from mature (>18 mm) or immature (<15 mm) follicles. Finally, we used the candidate miRNAs, miR-103a-3p and miR-10a-5p, to further investigate the relationship between their expression in FF and the outcomes of infertile patients undergoing IVF–ET treatment. The results of the bioinformatics analysis revealed 14 miRNAs that might directly regulate BDNF expression and might have a close relationship with oocyte development. BDNF was expressed at significantly lower levels in FF from immature follicles than in FF from mature follicles, and only the expression of miR-103a-3p and miR-10a-5p was negatively correlated with BDNF expression in FF. Moreover, in another cohort of 106 infertile women undergoing IVF-ET treatment, miR-103a-3p or miR-10a-5p expression predicted the developmental status of the corresponding oocytes in which high expression of miR-103a-3p or miR-10a-5p resulted in a poor quality of embryo on days 3 and 5 during the IVF-ET treatment. In conclusion, our study is the first to show that miR-103a-3p or miR-10a-5p negatively affects the maturation of oocytes by regulating the expression of BDNF in human FF. Additionally, the expression levels of miR-103a-3p or miR-10a-5p in FF may predict the outcomes of IVF, which are helpful for improving embryo selection and consequently the IVF success rate in the clinic.